The prognostic and clinicopathological significance of desmoglein 2 in human cancers: a systematic review and meta-analysis - Wang, Jiantao; Hao, Siyuan; Gu, Junjie; Rudd, Sean G.; Wang, Yan (PeerJ, 2022)
Objective The survival and clinicopathological significance of desmoglein 2 (DSG2) in various cancers is controversial. Thus, we performed this systematic review and meta-analysis to explore the preliminary prognostic value of DSG2. Methods Eligible studies were identified from databases including PubMed, the Cochrane Library, Embase, Web of Science and Scopus. Hand searches were also conducted in relevant bibliographies. We then extracted and pooled hazard ratio (HR) of overall survival (OS) and odds ratio (OR) of clinicopathological features. Results A total of 11 eligible studies containing 1,488 patients were included. Our results demonstrated that in non-small cell lung cancer (NSCLC), high DSG2 expression is associated with poor OS. However, in digestive system cancer and female reproductive system cancer, there were no statistically significant associations between OS and DSG2. Conclusions Based on the findings of this study, high DSG2 expression is associated with worse prognosis in patients with NSCLC, and thus DSG2 expression could be a biomarker for prognosis in NSCLC.
Keywords: Desmoglein 2; Cancer; Prognosis; Systematic review; Meta-analysis